Pemetaan Potensi Wilayah Untuk Pembangunan Observatorium di Jawa Timur Menggunakan Software ArcGIS - Cahyani, Hanis Intan (Program Studi Ilmu Falak UIN Sunan Ampel Surabaya, 2025)
East Java Province has diverse geographical conditions and several areas with low levels of light pollution, making it a potential location for the construction of an observatory. This study aims to map these potential areas using ArcGIS software. The research is a library research with a qualitative descriptive approach. The data used include light pollution data from the Light Pollution Maps (LPM) website, wind speed and cloud data from the Weather Spark website, elevation data from Google Earth, and topographic data from the Digital Elevation Model (DEM). Data collection was carried out through literature study and then analyzed using a descriptive method to identify areas that meet the criteria for observatory development. The results show that East Java has varied elevation levels and several regions with low light pollution. Based on the analysis, three main locations were identified as potential sites for observatory construction: Bromo National Park in Lumajang Regency, Ijen National Park in Bondowoso Regency, and Meru Betiri National Park in Jember Regency. These three locations meet the ideal criteria for an observatory, such as sufficient elevation, minimal light pollution, sparse settlements, and relatively stable climatic conditions.